Emotional responses to climate change information and their effects on policy support - Myers, Teresa A.; Roser-Renouf, Connie; Maibach, Edward (Frontiers in Climate, 2023)
Introduction As emotions are strong predictors of climate policy support, we examined multiple discrete emotions that people experience in reaction to various types of information about climate change: its causes, the scientific consensus, its impacts, and solutions. Specifically, we assessed the relationships between four types of messages and five discrete emotions (guilt, anger, hope, fear, and sadness), testing whether these emotions mediate the impacts of information on support for climate policy. Methods An online experiment exposed participants (N = 3,023) to one of four informational messages, assessing participants' emotional reactions to the message and their support for climate change mitigation policies as compared to a no-message control group. Results Each message, except the consensus message, enhanced the feeling of one or more emotions, and all of the emotions, except guilt, were positively associated with policy support. Two of the messages had positive indirect effects on policy support: the impacts message increased sadness, which in turn increased policy support, and the solutions message increased hope, which increased policy support. However, the solutions message also reduced every emotion except hope, while the impacts, causes, and consensus messages each suppressed hope. Discussion These findings indicate that climate information influences multiple emotions simultaneously and that the aroused emotions may conflict with one another in terms of fostering support for climate change mitigation policies. To avoid simultaneously arousing a positive motivator while depressing another, message designers should focus on developing content that engages audiences across multiple emotional fronts.